ATOMISTIC INVESTIGATION ON THE ROLE OF TEMPERATURE AND PRESSURE IN DIFFUSION WELDING OF AL-NI - Zaenudin, Mohamad; Abdulrazaq, Mohammed N.; Al-Zubaidi, Salah; Gamayel, Adhes; Sunardi, Ade (Institute for Research and Community Services, Institut Teknologi Bandung, 2020)
This paper presents an investigation of diffusion welding of aluminum and nickel at the atomic scale by utilizing molecular dynamics simulation. By employing several temperature and pressure values, the significant influence of the two could be obtained and thus the optimum parameter values could be obtained. The results showed that the bonding mechanism is mostly promoted by Al, in which the deformation and defects are involved. The results on both the mechanical properties and the evolution of the diffusion configuration showed that temperature has more impact compared to pressure. It was indicated that by raising the temperature to 700 K with the lowest pressure (50 MPa), both the mechanical properties and the evolution of the diffusion configuration showed a relatively significant difference. On the one hand, the deformation that occurs during welding, which is mostly caused by raising the temperature, obviously promotes joining and therefore more joining depth can be achieved, although it results in a curved diffusion zone at the interface. On the other hand, it also leads to a lower ultimate tensile strength. During the tensile test, raising the temperature also led to focusing the deformation in the diffusion zone, while a lower temperature resulted in a wider area of deformation.